RANCANGAN BENTUK KEPEMILIKAN BISNIS KELUARGA PT. X UNTUK MENJAGA KEBERLANGSUNGAN DI MASA DEPAN - Gandhatama, Lisia; Efferin, Sujoko (University of Surabaya, 2016)
This study was conducted to determine the differences and contradictions of what is happening in the family company that has been established since 1991 as well as any alternative that could be an option for the company to maintain its sustainability in the future. Therefore, researchers conducted a quite deep interview and observation of the perspective and aim shared by the two leaders in this company as well as the contradictions of what is happening in the company, not to forget the researcher also asked their opinion about the companys future. Other than that, the researcher also did a fairly long observation to the company operational activity as well as the personal relationship between the two within the family.This study is an applied research with qualitative method that uses interview and observation as data sources. In this study, it is known that there are 3 alternative forms of family business proper to be applied in this company. For each of the alternatives, researcher gave a consideration accompanied by the drawbacks and the benefits for each alternatives. The results provide an alternative that is deemed by the researcher to be the best alternative that can be applied in this family business, which will be a form of Parent-Subsidiary company. Each leader will manage and organize their own company without interference from other leaders. The expectancy with this case, each company can run well and in accordance with what is to be achieved by the leader.